Preparation and investigations on the thermal, structural and magnetic behavior of Co-Ce substituted Ni nanoferrites. (27th September 2019) - Qamar, Sabih; Yasin, Saima; Ramzan, Naveed; Iqbal, Tanveer; Akhtar, Majid Niaz
Abstract: Co-Ce doped Ni nanocrystalline ferrites having composition Ni 0.8 Ce 0.2 Co x Fe 2 − x O 4 with x = 0.00, 0.25, 0.50, 0.75, 1.00 were fabricated by sol gel auto combustion method. Synthesized samples were investigated by thermal gravimetric and differential thermal analysis (TGA-DTA), Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive analysis (EDX) and vibrating sample magnetometer (VSM) to study the phase, vibrational modes, structure, surface analysis and magnetic properties respectively. Structural parameters (lattice parameters, cell volume, crystallite size and micro strains) were also calculated from XRD recorded data. SEM images depicted that agglomerations in Co-Ce substituted Ni ferrites which may be due to presence of cerium ions and formation of particles irregular shape also confirmed the ferrites nanosized. Presence of metal and oxygen in respective ratio were confirmed by EDX analysis. Magnetic hysteresis loops were measured by VSM in order to find out the Yafet and Kittel (Y-K) angles, anisotropy constant, magnetic moments, coercivity, remanence and saturation magnetization. Magnetic hysteresis loops depicted the soft magnetic behavior of Co-Ce doped Ni nanocrystalline ferrites The properties of Co-Ce doped Ni ferrites may be auspicious for switching, core, security, sensing, chip inductor of multilayers, biomedical and absorption of microwave applications.